Perlindungan Hukum Terhadap Konsumen Pengguna Teknologi Finansial Berbasis Peer to Peer Lending Syariah di Indonesia - Delfa Violina; Renny Supriyatni (Universitas Serang Raya, 2021)
Today's technological developments are increasingly developing, one of the sectors affected by this technological development is the economic sector. Peer to Peer Lending is a product of technology in the economic sector. Considering that Indonesia is a country with a majority Muslim population, making Peer to Peer Lending experience a change from conventional to sharia. Peer to peer lending sharia must follows sharia principles based on the rules established by the Otoritas Jasa Keuangan and Fatwa Majelis Ulama Indonesia. The convenience provided by Peer to Peer Lending Syariah has the posibility to all the risks that exist, making the government try to be able to protect all parties with existing regulations. This research will be using normative juridical methods, which connected with all the theories, concepts, documents, and regulation which related to peer to peer lending syariah. Therefore, this journal aims to understand positive legal provisions related to the implementation of Peer to Peer Lending sharia and legal protection and legal action that can be taken by consumers based on the regulation of Peer to Peer Lending.